LOOTING IN THE 1998 DEMONSTRATION TO OVERTHROW PRESIDENT SOEHARTO ACCORDING TO ISLAMIC CRIMINAL LAW - Dewi Sinta Amalia; Enceng Arif Faizal; Yusup Azazy (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
In 1998, Indonesia experienced a period of mass riots across various regions. These riots were triggered by the multidimensional crisis the country was facing at the time, including an economic crisis, a legal crisis, a social crisis, and a political crisis. The objective of this study is to conduct an in-depth investigation into the May 1998 looting incidents by analyzing accountability and sanctions for the perpetrators. The research method employed is a normative legal approach using case studies, historical analysis, and conceptual analysis. The findings of this study indicate that the 1998 looting incident was not merely a criminal act committed by chance during the monetary crisis, but rather premeditated crimes, evidenced by the fact that the perpetrators were outsiders who arrived at the sites of the looting and by the nearly identical patterns of the incident across all locations where looting occurred. The perpetrators of the looting were a group of men who were carrying sharp weapons, stones, and fuel. Their actions constituted rebellion against the governments, with all the necessary elements fulfilled; the penalty for those who rebel is to be fought against, while the penalty for those who take advantage of the looting situation is criminal punishment for robbery.